Pengembangan Media Video Pembelajaran pada Mata Pelajaran Ilmu Pengetahuan Sosial (IPS) Kelas VII di Sekolah Menengah Pertama - Riska Yulia Sari; Rayendra, Rayendra; Zen, Zelhendri; Eldarni, Eldarni (Jurnal Pendidikan Tambusai, 2024)
Video media is a type of audio-visual learning media that includes images, sound and movement, which can convery learning message to students. The use of learning media has not been effective, which makes it difficult for teachers to explain the material to students. One of the competencies of Educational Technology is to become a learning media developer. This development reserach follows the Borg&Gall model, and is tested for the validity and practicality of the media develop. These stages include: (1) planning, (2) initial product, (3) product validation, (4) testing, and (5) final product. The average score of this learning video media product by material expert was 4,84, categorized as “Very Suitable”. Furthermore, from media experts, the average score was obtained from media expert I was 4,73 and media expert II was 4,60, from this score the media could be categorized as “Very Feasible”. Meanwhile, the practicality test shows that this learning video media product received a positive response from users by obtaining an average score of 4,62 with a percentage of 92,40% with the criteria “Very Practical”.